ANALISIS DAMPAK LITERASI KEUANGAN, INKLUSI KEUANGAN DAN STRATEGI PEMASARAN TERHADAP KINERJA UMKM DI KOTA MEDAN - Salsabila, Lira Putri; Parhusip, Austin Alexander (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to analyze the effect of financial literacy, financial inclusion, and marketing strategy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. MSMEs play a strategic role in the national economy; however, they still face challenges such as low financial literacy, limited access to financial services, and suboptimal marketing strategies. This research employs a quantitative approach with a survey method. The sample consists of 100 culinary MSME actors in Medan City selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The results indicate that financial literacy, financial inclusion, and marketing strategies have a positive and significant influence on MSME performance both partially and simultaneously. These findings suggest that enhancing financial literacy, expanding access to formal financial services, and implementing appropriate marketing strategies can strengthen the competitiveness and sustainability of MSMEs in Medan City. This study is expected to serve as a reference for MSMEs, policymakers, and financial institutions in formulating more effective MSME development strategies. Keywords: Financial Literacy, Financial Inclusion, Marketing Strategy, MSME Performance, Medan